DETEKSI PENGGUNAAN FORMALIN PADA DAGING AYAM DI PASAR TRADISIONAL, PASAR SWALAYAN DAN PEDAGANG KELILING DI KOTA YOGYAKARTA - , RAEGINA PANDU YUDHANTI, drh. Heru Susetya, MP., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Research on residual formalin on chicken meat in traditional markets, supermarkets and pitchman in Yogyakarta is aiming to find out the prevalensi of the use of formalin on chicken meat in traditional markets, self-service and pitchman of Yogyakarta, as well as factors related to the occurrence. The sample used is 98 chicken meat obtained from 11 traditional markets, 19 supermarkets and 23 pitchman in Yogyakarta are chosen at random. Each sample was tested using reagent fenilhidrazin. The testing done in duplo. Formaldehyde residue testing methods using fenilhidrazin that is by weighing 10 grams of meat, add 10 ml aquadest, mashed. Supernatan is taken and put into test tubes and then add 3 drops of a solution of fenilhidrazin 0.5%, plus 2 drops of a solution of sodium nitroprusid 5%, and 3 drops of a solution of NaOH plus 10%. If the solution is green-blue and finally turns into a red-orange color, then the sample is positive and if the yellow negative samples. This research results showed that 6 of 98 samples of chicken meat containing formalin, with positive prevalence of 6.1%. Chicken meat derived from formalin positive traditional markets. Chi-Square analysis showed where the sale gave a significant role against the presence of formalin on chicken meat that are researched by the value ï£2= 6,222, of factors research (questionnaire) shows the origin of chicken meat sales, location environment of the sale, place of the sale, knowledge of the meat hygiene and treatment of the meat that is not sold out to give a role to the presence of negative formalin on chicken meat supermarket and pitchman who researched.